Fermented tea residue improved growth performance, liver antioxidant capacity, intestinal morphology and resistance to Aeromonas hydrophila infection in juvenile largemouth bass (Micropterus salmoides) - Jiang, Li; Zhou, Xinhong; Yu, Jing; Bao, Songsong; Li, Jin; Wu, Qiuhong; Wu, Mengjia; Wang, Yachao; Liu, Bo (Frontiers in Marine Science, 2022)
The study aimed to evaluate the effects of fermented tea residue (FT) on growth performance, intestinal morphology, liver antioxidant capacity and Aeromonas hydrophila infection in juvenile Largemouth bass. A total of 240 fish were randomly distributed in 12 tanks with 20 fish per tank (4 treatments with 3 replications) and fed with diets FT at the rate of 0 (control), 2, 4 and 6%. The weight gain rate (WGR), specific growth rate (SGR) and intestinal villi height (VH) of juvenile largemouth bass were significantly higher than those of the control group after feeding FT (P< 0.05); meanwhile, the liver superoxide dismutase (SOD), glutathione peroxidase (GSH-PX) and catalase (CAT) activities of juvenile largemouth bass were significantly higher and the malondialdehyde (MDA) levels were significantly lower than those of the control group after feeding FT (P< 0.05). Mortality occurred in all groups of largemouth bass after the injection of A.hydrophila, but feeding FT reduced the cumulative mortality compared with the control group (P< 0.05). In juvenile largemouth bass infected with A.hydrophila, the relative mRNA expression of the intestinal anti-inflammatory factors IL-10 and TGF-α was significantly higher and that of the pro-inflammatory factors IL-1, IL-15, IL-8, and TNF-α was significantly lower (P< 0.05). In summary, it can be seen that a 2% FT addition can improve the liver antioxidant capacity of juvenile largemouth bass, enhance the resistance to A.hydrophila and increase the growth of largemouth bass.